1998
DOI: 10.1021/bi981958y
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Two Electron-Transfer Sites in Ascorbate Peroxidase Using Chemical Modification, Enzyme Kinetics, and Crystallography

Abstract: Chemical and mutagenic modification combined with X-ray crystallography has been used to probe the ascorbate binding site in ascorbate peroxidase (APX). Chemical modification of the single Cys residue in APX with Ellman's reagent (DTNB) blocks the ability of APX to oxidize ascorbate but not other small aromatic phenolic substrates. DTNB-modified APX (APX-TNB) exhibits only 1.3% wild-type activity when ascorbate is used as the substrate but full activity when aromatic substrates, guaiacol or pyrogallol, are use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
82
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(90 citation statements)
references
References 17 publications
7
82
1
Order By: Relevance
“…In addition, the C32S mutant exhibits similar activity with guaiacol but, in contrast, there is a dramatic decrease of ascorbate oxidation. All these data suggest that this residue is located close to the ascorbatebinding site confirmed crystallographically (Sharp et al 2003a) with the binding of aromatic substrates such as guaiacol occurring at a different site (Mandelman et al 1998;Lad et al 2002;Sharp et al 2004).…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…In addition, the C32S mutant exhibits similar activity with guaiacol but, in contrast, there is a dramatic decrease of ascorbate oxidation. All these data suggest that this residue is located close to the ascorbatebinding site confirmed crystallographically (Sharp et al 2003a) with the binding of aromatic substrates such as guaiacol occurring at a different site (Mandelman et al 1998;Lad et al 2002;Sharp et al 2004).…”
Section: Discussionsupporting
confidence: 53%
“…The observed inactivation of APX in presence of sulfhydryl components is probably not due simply to an alteration of APX Cys32. Indeed, in the tested conditions, incubation of APX with sulfhydryl groups altered both guaiacol and ascorbate oxidation whereas Cys32 is only involved in the ascorbate binding site (Mandelman et al 1998;Lad et al 2002;Sharp et al 2003aSharp et al , b, 2004. Taken together, these data suggest that thiyl radicals induce large changes in APX (particularly in the vicinity of Trp residues) leading to the inactivation of the enzyme.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…It has been reported that pea (Pisum sativum) cAPX possesses two binding sites for ascorbate, with different affinities for the substrate (Lad et al, 2002). The high-affinity site is located in the vicinity of the Cys-32 residue (Mandelman et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Although steady state kinetic analyses have been a fairly prominent feature of most of the early literature on APX (reviewed in [7]), presteady-state kinetic data has been very much more limited [8][9][10][11][12][13]. Formation of Compound I for wild-type rAPX [14] (Fig.…”
Section: Catalytic Mechanismmentioning
confidence: 99%